Sonora: A Platform for Continuous Mobile-Cloud Computing - Chen, Xiuwei; Beschastnikh, Ivan; Zhuang, Li; Yang, Fan; Qian, Zhengping; Zhou, Lidong; Shen, Guobin; Shen, Jacky (2012)
This paper presents Sonora, a platform for mobile-cloud computing. Sonora is designed to support the development and execution of continuous mobile-cloud services. To this end, Sonora provides developers with stream-based programming interfaces that coherently integrate a broad range of existing techniques from mobile, database, and distributed systems. These range from support for disconnected operation to relational and event-driven models. Sonora's execution engine is a fault-tolerant distributed runtime that supports user-facing continuous sensing and processing services in the cloud. Key features of this engine are its dynamic load balancing mechanisms, and a novel failure recovery protocol that performs checkpoint-based partial rollback recovery with selective re-execution. To illustrate the relevance and power of the stream abstraction in describing complex mobile-cloud services we evaluate Sonora's design in the context of two services. We also validate Sonora's design, demonstrating that Sonora is efficient, scalable, and provides responsive fault tolerance.